Rapid detection of heavy metals in incineration bottom ash - Koh, Edwin Fang Kai (2015)
This project serves to develop a means for rapid detection of heavy metals in incineration bottom ash, allowing for rapid characterisation of it for utilisation or recycle for other applications. The focus of this project was divided into two general sections. The first part was to develop a means to reduce the time required for toxicity characteristic leaching procedure (TCLP). This was achieved through the use of sonochemistry to speed up the ±18hours extraction period required in a method labelled as sonoleaching. Preliminary investigations have shown that sonoleaching is indeed an effective method for the leaching of heavy metals. However, there were further studies required in order to better match the results from TCLP. The second part of the project was focused on the analysis of heavy metals from leachates obtained. This was done using electrochemistry or to be more precise the use of square wave anodic stripping voltammetry (SWASV) and screen printed electrodes manufactured by Drop Sens. Out of the different types of electrodes studied the carbon electrode (DRP-110) has been found to be most effective in the rapid detection of heavy metals and also was most financially viable. The results indicated that the electrode in question was able to detect Zn, Pb and Cd simultaneously allowing for a well-defined calibration curve to be established from standard mixtures. Overall, the integration of sonoleaching and electrochemical detection yields positive results. The advent of sonoleaching was able to greatly reduce the leaching time required. The combination of these two methods provided a feasible system for the detection of heavy metals on site. Nonetheless, further studies are required to better match the TCLP results with ultrasonic methods. Also, better understanding of various disturbances to electrochemical detection needs to be studied in greater detail before the system can be established